Thermal Oxidation Preparation of Doped Hematite Thin Films for Photoelectrochemical Water Splitting - Song Li; Jiajia Cai; Yudong Mei; Yuping Ren; Gaowu Qin (International Journal of Photoenergy)
Sn- or Ge-doped hematite thin films were fabricated by annealing alloyed films for the purpose of photoelectrochemical (PEC) water splitting. The alloyed films were deposited on FTO glass by magnetron sputtering and their compositions were controlled by the target. The morphology, crystalline structure, optical properties, and photocatalytic activities have been investigated. The SEM observation showed that uniform, large area arrays of nanoflakes formed after thermal oxidation. The incorporation of doping elements into the hematite structure was confirmed by XRD. The photocurrent density-voltage characterization illustrated that the nanoflake films of Sn-doped hematite exhibited high PEC performance and the Sn concentration was optimized about 5%. The doped Ge4+ ions were proposed to occupy the empty octahedral holes and their effect on PEC performance of hematite is smaller than that of tin ions.